Empowering Village Government in Realized Village Autonomy According to Law Number 6 of 2014 Concerning Villages : Case Study of the Natumingka Village Government, Borbor District, Toba Regency - Yoel Marsada Simanjuntak; Hisar Siregar; Januari Sihotang (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the empowerment of village governments in realizing village autonomy as regulated in Law Number 6 of 2014 concerning Villages, with a case study focus on the Natumingka Village Government, Borbor District, Toba Regency. The law affirms villages as government entities that have the authority to regulate and manage community interests based on ancestral rights and local autonomy, which aims to strengthen democratic, participatory, and independent village governance. This study also examines changes and improvements to regulations that occurred with the enactment of Law Number 3 of 2024 Jo, which emphasizes the strategic role of villages in national development and optimizes the authority and support for the empowerment of village government officials and their communities.